If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 9 = 6x + 16 Reorder the terms: 9 + 13x = 6x + 16 Reorder the terms: 9 + 13x = 16 + 6x Solving 9 + 13x = 16 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 9 + 13x + -6x = 16 + 6x + -6x Combine like terms: 13x + -6x = 7x 9 + 7x = 16 + 6x + -6x Combine like terms: 6x + -6x = 0 9 + 7x = 16 + 0 9 + 7x = 16 Add '-9' to each side of the equation. 9 + -9 + 7x = 16 + -9 Combine like terms: 9 + -9 = 0 0 + 7x = 16 + -9 7x = 16 + -9 Combine like terms: 16 + -9 = 7 7x = 7 Divide each side by '7'. x = 1 Simplifying x = 1
| .6(r-2)=7.2 | | 4x+21=17 | | (-3x)=-9 | | y=10(-5)-1 | | 4(3a+6)=-5 | | Y=fox+a | | 6x+7y=-7 | | C=3.25+0.75(y-3) | | 3(-2b-4)=6 | | 2(x-3)-5x=9 | | 9(x+3)-7=25-5x-5+14x | | -2(n-8)=25 | | c=.7h(285.7) | | 5(2x+4)=14 | | x+15=4x+24 | | 3(-4x+2)=30 | | 3(-4+2)=30 | | 11-7=2y-6 | | -3x+12=-4x+10 | | Z=x^2-2y | | -3(c+2)=6 | | 2x+19=100 | | .8x+6.6=1.4 | | sn+7=21 | | -5(x-3)=0 | | 12x+65=110 | | 4x+8-2x=2(x+4) | | x^2+3x+(k+2)=0 | | 2(3x+4)+5=20 | | 10p+2-p=-7 | | 9x-6-5x=5x-5 | | 3x-8=27-4x |